Clinical characteristics and haemodynamic state of patients undergoing interhospital transfer for postpartum haemorrhage: A study of a single-centre helicopter emergency medical service. (January 2022) - Giacalone, S.; Kottmann, A.; Darioli, V.; Carron, P.N.; Desseauve, D.; Albrecht, R.; Pasquier, M.
Abstract: Objective: Uterine artery embolization is an attractive option for the management of postpartum haemorrhage, however it is not available in every hospital. We compared the clinical characteristics and haemodynamic state of patients with postpartum haemorrhage, before and after helicopter transfer to a tertiary hospital for possible uterine artery embolization. We also analysed whether the type of treatment could modify the outcome. Study design: Between 1999 and 2019 in Switzerland, we retrospectively found 82 consecutive patients with postpartum haemorrhage who were transferred by a physician-staffed helicopter emergency medical service to the tertiary hospital for potential uterine artery embolization. The collected data included the type of delivery, estimated blood loss, shock index and blood lactate levels before transfer and at destination, uterine artery embolization rate and hospital mortality rate. Our primary outcome was to describe the clinical characteristics, outcomes and haemodynamic state of the patients with postpartum haemorrhage before and after helicopter transfer. Our secondary outcome was to report the treatments performed at the tertiary hospital. The collected data were analysed with Stata version 14 (Stata Corporation, College Station, TX, USA). Continuous data are compared by using the Student's t -test or the Mann-Whitney U test, as appropriate. Results: We included 69 patients. Postpartum haemorrhage occurred after vaginal delivery in 38 cases (55%). Blood loss prior to transfer exceeded 2 L in 34% of cases. The median shock index was 1 (IQR 0.8–1.1) before transfer and 0.9 (IQR 0.8–1.1) after transfer (p = 0.41). The median lactate level was 2.9 mmol/L (IQR 2.1–6.8) before, and 2.1 mmol/L (IQR 1.55–3.5) after transfer (p = 0.90). Forty-four patients underwent uterine artery embolization (64%), with an overall success rate of 93%. One patient died (1.4%), from a haemorrhagic shock of abdominal origin. Conclusions: Interhospital helicopter transfer of patients with postpartum haemorrhage to a tertiary hospital seems to be safe in our setting, despite a significant proportion of patients exhibiting signs of haemodynamic instability. Decision criteria would be helpful to better guide choices regarding the transfer of patients with postpartum haemorrhage.